Fecal Microbiota Transplantation - Cheng, Yao-Wen; Fischer, Monika (Clinics in Colon and Rectal Surgery, 2023)
Fecal microbiota transplantation (FMT) is the process of transplanting stool from a healthy donor into the gut of a patient for therapeutic purposes. Current guidelines recommend FMT for the prevention of multiply recurrent Clostridioides difficile infection (CDI) after two recurrences, with cure rates approaching 90%. Emerging evidence also supports the use of FMT in the management of severe and fulminant CDI, resulting in decreased mortality and colectomy rates compared with standard of care approach. FMT shows promise as salvage therapy for critically-ill, refractory CDI patients who are poor surgical candidates. FMT should be considered early in the clinical course of severe CDI, preferably within 48 hours of failing to respond to antibiotic therapy and volume resuscitation. Besides CDI, ulcerative colitis was more recently identified as a potential treatment target for FMT. Several live biotherapeutics for microbiome restoration are on the horizon.
Keywords: Clostridioides difficile; colitis; toxic megacolon; fecal microbiota transplantation; colonoscopy; colectomy